Vaccination Trial For Egg Drop Syndrome - 1976 (Eds -'76) - Suresh, P.; Shoba , K.; Rajeswar , J. Johnson (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A vaccination trial for Egg Drop Syndrome - 1976 (EDS -'76) was conducted in commercial layers. The commercial vaccine used in this study was found protective against a local isolate. The birds in group I which received a booster dose three weeks after first vaccination did not excrete any virus after challenge throughout the observation period but birds in group II which received single vaccination alone excreted the virus upto 9 days PI. There was no egg abnormalities detected in vaccinated birds. The virus excretion in control group was present upto 15 days PI and the egg abnormalities were noticed 25 days PI. The post mortem examination and histopathological findings were supportive of EDS -'76 virus infection in control group.
Keywords: Egg Drop Syndrome - 1976; Inactivated Vaccine; Serology; Virus Shedding